Business incubation training for pig and cattle artificial insemination service providers in Mai Son District, Son La Province, Vietnam - Le, Pham Thi; Trinh, Nguyen Thi; Tranh, Lo Quang; Marshall, Karen (International Livestock Research Institute, 2024)
Launched in Vietnam in 2022 until the end of 2024, the CGIAR Initiative on Sustainable Animal Productivity for Livelihoods, Nutrition, and Gender Inclusion (SAPLING) aims to enhance the livestock sector in Son La Province, situated in northwest Vietnam. The interventions were implemented through five work packages (WP), with WP1 concentrating on providing technical advancements in three key pillars of livestock productivity: genetics, feed and forages, and animal health. Alongside offering technical assistance to farmers and enhancing the skills of veterinary personnel, the WP1 – Genetics component has established a cooperative of cattle artificial insemination (AI) service providers to improve the delivery of AI services in the region. The cooperative has four members, two men and two women, those belong to the Kinh, Thai and Mong ethnic groups. Each member was supported by the project with a small nitrogen tank, an inseminating gun, hormone and other equipment for heating synchronization and performing AI. From May to October 2024, a business incubation training course was held for members of the AI service provider cooperative to improve their professionalism and increase profitability. This opportunity was also extended to four additional veterinarians who are interested in providing AI services and joining the cooperative. All eight participants had previously completed technical training courses organized by the National Institute of Animal Husbandry (NIAS) and received certificates, enabling them to professionally deliver AI services. The training course focused on three areas: i. Training on business plans ii. Training on marketing and sale skills iii. Monthly meeting and coaching